(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
ABSTRACT Aim/Purpose This study investigates customer sentiment toward telecom Quality of Service Delivery (QoSD) in Ghana by integrating dual sentiment, that is, an expressed emotional sentiment from customer narratives and experienced service sentiment derived from SERVQUAL ratingsinto a unified service quality evaluation framework. Background Although SERVQUAL-based research consistently links service quality dimensions to customer satisfaction, far less is known about how emotional expressions interact with cognitive service evaluations in developing markets. This gap limits understanding of how users interpret service failures and form satisfaction judgments in resource-constrained telecom environments. Methodology A nationwide survey of 536 mobile users was analyzed using a hybrid analytical approach: (1) natural language processing (NLP) sentiment scoring of open-ended responses, and (2) construction of a Service Sentiment Index (SSI) based on standardized SERVQUAL dimension scores. Mediation analysis using Hayes’ PROCESS tested whether experienced sentiment serves as a psychological pathway linking reliability to overall satisfaction. Contribution The study introduces and empirically validates a dual-sentiment framework for telecom QoSD assessment, demonstrating significant divergence between customers’ expressed emotional sentiment and their experienced service sentiment. It extends the SERVQUAL model by incorporating affective evaluation processes and provides empirical evidence that sentiment partially mediates the reliability–satisfaction relationship. Findings Expressed sentiment was predominantly negative (56.5%), whereas SSI reflected more moderate evaluations. Reliability, assurance, and empathy emerged as key predictors of both sentiment and satisfaction. Mediation results confirmed that experienced sentiment explains a substantial portion of the total effect of reliability on satisfaction, supporting a dual cognitive–affective interpretation of QoSD. Recommendations for Practitioners Telecom providers should prioritize network reliability, transparent communication, and empathetic customer engagement to address emotional dissatisfaction. The presence of strong negative expressed sentimenteven among customers reporting moderate satisfactionsignals potential reputational and churn risks requiring proactive management. Recommendations for Researchers Researchers should integrate text analytics with psychometric models in service quality studies and further examine sentiment as a mediator across diverse service industries and cultural settings. Impact on Society Understanding sentiment divergence enhances the design of customer-centric QoS interventions, strengthens regulatory oversight, and supports the development of more responsive telecom service policies in emerging markets. Future Research Longitudinal studies should explore sentiment trajectories over time, while cross-market comparative research should validate the generalizability of the dual-sentiment framework across other developing and developed economies.